Greco-Roman cities at the crossroads of cultures : the 20th anniversary of Polish-Egyptian conservation mission El-Alamein - Bakowska-Czerner, Grazyna, (Archaeopress archaeology.)
The ancient town discovered at the site of today's Marina el-Alamein (located on the northern coast of Egypt) developed from the 2nd century BC to the 6th century AD. It found itself at the crossroads of several civilisations: Hellenic, later replaced by Roman, and ultimately Christian, and was always strongly influenced by Egyptian tradition. A variety of cultures appeared and met here and grew in strength - then their significance weakened - but they always co-existed and influenced one another. The syncretism prevailing here is notable in the spheres of art, architecture, religion and worship. 2015 marked thirty years since the discovery of the remains of the ancient city, which, for many centuries, had been unknown to the world. The remains were found unexpectedly during the preparatory work for the construction of a modern tourist settlement on the Mediterranean coast, and the significance and extraordinary value of the discovery was immediately recognised. Now the ancient city, and the historic remains of its buildings, are gradually coming to light. The papers in the present volume encompass interdisciplinary reviews of both new and long-term studies carried out in various regions of the ancient world. The papers present research that was conducted in different regions ranging from ancient Mauritania, through Africa, Egypt, Cyprus, Palestine, Syria, as well as sites in Crimea and Georgia. The topography of cities, the architecture of public buildings, as well as houses and their decor - architectural, sculptural and painted - are presented. Religious syncretism and the importance of ancient texts are discussed. Several articles are devoted to the study of Marina el-Alamein; others talk about ancient Alexandria, Deir el-Bahari, Hermopolis Magna, Bakchias, Pelusium, Kom Wasit, Berenike, Ptolemais, Apollonia, Palmyra, Nea Paphos, as well as Chersonesus Taurica and Apsarus.